The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0080-62342004000400003
|View full text |Cite
|
Sign up to set email alerts
|

Infecção de sítio cirúrgico no seguimento pós-alta: impacto na incidência e avaliação dos métodos utilizados

Abstract: It is a prospective study in two teaching hospitals. They accompanied 501 admitted patients who were submitted to the surgery of the digestive system from August 2001 to March 2002. In the period of the study, 140 surgical site infections (SSIs) were diagnosed. Thirty-one SSIs were diagnosed in the hospital and 109 after the discharge. The incidence of SSIs was of 6.2%, rising for 28.0%, with postdischarge surveillance. The methods of postdischarge surveillance are also discussed and among the several options,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 8 publications
0
10
0
15
Order By: Relevance
“…In another prospective study in two teaching hospitals, 501 patients underwent gastrointestinal surgery, and 140 SSI cases were diagnosed, of which, 31 reported during hospitalization and 109 during post-discharge, with incidence rates of 6.2% and 28%, respectively (11) . Without completing the post-discharge follow-up, 77.9% of the SSI cases would not be notified (11) . This shows that if the post-discharge surveillance had not been performed, the overall rate of SSI would be greatly underreported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another prospective study in two teaching hospitals, 501 patients underwent gastrointestinal surgery, and 140 SSI cases were diagnosed, of which, 31 reported during hospitalization and 109 during post-discharge, with incidence rates of 6.2% and 28%, respectively (11) . Without completing the post-discharge follow-up, 77.9% of the SSI cases would not be notified (11) . This shows that if the post-discharge surveillance had not been performed, the overall rate of SSI would be greatly underreported.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the SSI rates in colon surgery varied from 3.5 to 21.3%, and are pointed as the largest SSI rates among elective procedures (5)(6)(7)(8)(9)(10)(11) . But diagnosing SSI only during hospital stay has not provided actual rates, which may underestimate the real values, as shown in a national study that notified 75% of SSI during post-discharge surveillance (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical site infecti on is the second most important infecti on in hospitalized pati ents, leading to a rise in treatment costs, increasing the probability of surgical re-interventi ons and increasing mortality rates (10) . Although risk factors for infecti on development in surgical pati ents can be esti mated, its predicti on, with high probability levels, sti ll represents a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is the HICC's responsibility to perform epidemiologic surveillance for every patient, especially those with higher infection risks, such as surgical patients. It is also suggested that surveillance be done through prospective methods, such as the active, systematic, and continuous search for hospital infections and their dissemination (1)(2)(3)(4)(5) .…”
Section: Programs (Hicp) Developed By Hospital Infectionmentioning
confidence: 99%
“…Studies that performed surgical patient follow-up after discharge estimate that 12 to 84% of the SSI appears after discharge. This causes underreported rates, since surveillance occurs exclusively during hospitalization (1)(2)(4)(5)(6)(7)(8) .…”
Section: Programs (Hicp) Developed By Hospital Infectionmentioning
confidence: 99%